High-temperature antioxidant welding wire for laser welding and preparation process thereof
Patent Information
- Application Number
- CN202610902183.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-09-18
AI Technical Summary
传统不锈钢焊丝、普通合金焊丝在高温焊接环境下,表面极易发生氧化,形成疏松氧化层,进而导致焊缝出现气孔、夹渣、裂纹等缺陷,同时焊丝在储存过程中易受潮锈蚀,影响送丝稳定性与焊接效果
本发明的激光焊接用高温抗氧化焊丝及其制备工艺,通过将Cr粉、Ni粉、Al粉、Ti粉、Y粉、Si粉、Mo粉、Fe粉以及B粉分别烘干,烘干后放入混料机中,氩气保护下混合,得到芯部药粉,将不锈钢带轧制成U型槽,填充芯部药粉后挤压闭合U型槽,得到焊丝坯料,对焊丝坯料进行多道次冷拔,冷拔后进行退火处理,再经机械抛光,得到基础焊丝,将基础焊丝依次用丙酮、无水乙醇超声清洗并烘干,匀速通过包覆液槽进行涂覆,经预烘干和热风固化,得到激光焊接用高温抗氧化焊丝;激光焊接用高温抗氧化焊丝通过高温合金药芯、不锈钢包覆皮以及耐高温芳香族聚酰胺涂层的协同作用,具有优异的高温抗氧化性、焊接稳定性和使用可靠性,能够在激光焊接的高温环境下有效抑制焊丝及焊缝金属氧化,减少气孔、裂纹、夹杂等焊接缺陷,显著提升焊接接头的强度、韧性与耐高温腐蚀性能;涂层光滑致密、附着力强,可隔绝空气与水汽,延长焊丝储存寿命,同时降低送丝阻力,保证激光焊接过程连续稳定、送丝顺畅;焊丝成分均匀、组织致密、直径精度高,焊接成型美观,熔敷金属性能稳定,能够满足高温工况下关键构件对激光焊接接头的高性能要求,整体实用性强、应用前景广阔。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-temperature oxidation-resistant welding wire, specifically to high-temperature oxidation-resistant welding wire for laser welding and its preparation process. Background Technology
[0002] Laser welding boasts advantages such as high precision, a small heat-affected zone, and high welding efficiency, making it widely used in high-end equipment manufacturing. As a key filler material in the laser welding process, the high-temperature oxidation resistance of the welding wire directly determines the weld formation quality and joint lifespan. Traditional stainless steel welding wire and ordinary alloy welding wire are highly susceptible to surface oxidation under high-temperature welding environments, forming a loose oxide layer. This leads to defects in the weld such as porosity, slag inclusions, and cracks. Furthermore, the welding wire is prone to moisture and corrosion during storage, affecting wire feeding stability and welding results.
[0003] While existing flux-cored welding wires have improved their high-temperature performance to some extent through alloy system optimization, they lack a stable and effective surface protection structure, and still suffer from insufficient thermal stability and easy decomposition and fuming under the instantaneous high temperature of lasers. Some organic-coated welding wires have poor temperature resistance, weak adhesion to the metal substrate, and are prone to peeling and flaking, making it difficult to balance high-temperature oxidation resistance, storage stability, and welding processability.
[0004] Therefore, developing a laser welding wire that combines excellent high-temperature oxidation resistance, strong coating adhesion, and stable welding formation is of great engineering application value for improving the quality and reliability of laser welding joints. Summary of the Invention
[0005] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a high-temperature anti-oxidation welding wire for laser welding and its preparation process.
[0006] The objective of this invention can be achieved through the following technical solutions: In the first aspect, this application provides a high-temperature oxidation-resistant welding wire for laser welding, which is composed of a core powder, an outer coating, and a coating layer; The core powder comprises the following components in parts by weight: Fe powder 54-60 parts, Cr powder 24-26 parts, Ni powder 12-14 parts, Al powder 3-4 parts, Ti powder 1.2-1.8 parts, Y powder 0.10-0.13 parts, Si powder 1.0-1.2 parts, Mo powder 0.7-1.0 parts, B powder 0.003-0.005 parts; The outer cladding is made of H1Cr21Ni10Mn6 stainless steel strip; The coating is applied to the outer surface of the outer skin and is an aromatic polyamide resin. The coating is prepared by coating a welding wire coating solution made of aromatic polyamide resin and N,N-dimethylacetamide at a ratio of 1g:9mL. The aromatic polyamide is prepared by the following steps: Step a1: Add o-chlorotrifluorotoluene and concentrated sulfuric acid to a single-necked flask, stir for 30-35 min under ice bath conditions and stirring rate of 300-400 r / min, then add the mixed solution dropwise, and continue the reaction for 3-5 h after warming to room temperature. After the reaction is completed, extract in ice water, wash three times with saturated sodium chloride solution, separate the liquid to obtain the lower oily substance, and purify by column chromatography with petroleum ether eluent to obtain 2-chloro-5-nitrotrifluorotoluene. Step a2: Add phenoxazine, anhydrous potassium carbonate, and N,N-dimethylformamide to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection. Under conditions of 75-80℃ and stirring rate of 300-400 r / min, add 2-chloro-5-nitrotrifluorotoluene and react at 140-150℃ for 24-25 h. Then pour into ice water and let stand to crystallize. After filtration, place the solid in a vacuum drying oven and dry at 80-85℃ for 2-3 h. Separate and purify by column chromatography with petroleum ether eluent, and then recrystallize with ethanol to obtain intermediate I.
[0007] Step a3: Add intermediate I, palladium on carbon catalyst and anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube and constant pressure dropping funnel. Purge with nitrogen for protection. Under the conditions of 55-60℃ and stirring rate of 300-400 r / min, add hydrazine hydrate dropwise and react for 24-25 h at 70-80℃. Filter while hot, pour the filtrate into ice water to allow crystallization. After filtration, place the solid in a vacuum drying oven and dry at 80-85℃ for 2-3 h to obtain intermediate II.
[0008] Step a4: Add intermediate II, anhydrous potassium carbonate, and N,N-dimethylformamide to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection. Under conditions of 75-80℃ and stirring rate of 300-400 r / min, add 2-chloro-5-nitrotrifluorotoluene. React at 140-150℃ for 24-25 h. Pour into ice water and allow to stand for crystallization. Filter and wash with deionized water until neutral. Recrystallize in dichloromethane. After filtration, place the solid in a vacuum drying oven and dry at 80-85℃ for 2.5-3.5 h to obtain intermediate III.
[0009] Step a5: Add intermediate III, palladium on carbon catalyst and anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube and constant pressure dropping funnel. Purge with nitrogen for protection. Under the conditions of 55-60℃ and stirring rate of 300-400 r / min, add hydrazine hydrate dropwise and react for 24-25 h at 70-80℃. Filter while hot, pour the filtrate into ice water to allow crystallization, and vacuum dry at 70-80℃ for 3-4 h. Purify by column chromatography with mixed eluent to obtain diamine monomer.
[0010] Step a6: Add the diamine monomer, terephthaloyl chloride, and N,N-dimethylacetamide to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir for 60-70 min in an ice bath at a stirring rate of 300-400 r / min. Add pyridine, remove the ice bath, allow to rise naturally to room temperature, and continue stirring for 24-25 h. After the reaction is complete, pour into methanol, stir to precipitate solid, filter and collect the solid. Extract the solid with methanol at 110℃ for 24 h, filter, and place the solid in a vacuum drying oven at 85-90℃ for 4-5 h to obtain aromatic polyamide.
[0011] In a preferred embodiment of the present invention, the ratio of o-chlorotrifluorotoluene, concentrated sulfuric acid and the mixed solution used in step a1 is 0.25-0.50 mol: 42-84 mL: 84-168 mL.
[0012] In a preferred embodiment of the present invention, the mixed solution in step a1 is a solution of concentrated sulfuric acid and concentrated nitric acid mixed in a volume ratio of 1:1.
[0013] In a preferred embodiment of the present invention, the concentrated sulfuric acid in step a1 has a mass fraction of 98% and the concentrated nitric acid has a mass fraction of 68%.
[0014] In a preferred embodiment of the present invention, the ratio of phenoxazine, anhydrous potassium carbonate, N,N-dimethylformamide and 2-chloro-5-nitrotrifluorotoluene used in step a2 is 0.2-0.4 mol: 0.2-0.4 mol: 240-480 mL: 0.2-0.4 mol.
[0015] In a preferred embodiment of the present invention, the ratio of intermediate I, palladium on carbon catalyst, anhydrous ethanol and hydrazine hydrate in step a3 is 0.01-0.02 mol: 0.2-0.4 g: 40-80 mL: 20-40 mL.
[0016] In a preferred embodiment of the present invention, the palladium-on-carbon catalyst in step a3 has a palladium content of 5%.
[0017] In a preferred embodiment of the present invention, the ratio of intermediate II, anhydrous potassium carbonate, N,N-dimethylformamide and 2-chloro-5-nitrotrifluorotoluene in step a4 is 0.05-0.10 mol: 0.1-0.2 mol: 100-200 mL: 0.12-0.24 mol.
[0018] In a preferred embodiment of the present invention, the ratio of intermediate III, palladium on carbon catalyst, anhydrous ethanol and hydrazine hydrate in step a5 is 0.01-0.02 mol: 0.2-0.4 g: 40-80 mL: 20-40 mL.
[0019] In a preferred embodiment of the present invention, the mixed eluent in step a5 is a solution of petroleum ether and dichloromethane mixed in a volume ratio of 3:1.
[0020] In a preferred embodiment of the present invention, the palladium-on-carbon catalyst in step a5 has a palladium content of 5%.
[0021] In a preferred embodiment of the present invention, the ratio of the diamine monomer, terephthaloyl chloride, N,N-dimethylacetamide and pyridine in step a6 is 1-2 mol: 1-2 mol: 3.7-7.4 L: 0.1-0.2 L.
[0022] Secondly, this application provides a process for preparing high-temperature oxidation-resistant welding wire for laser welding, including the following steps: Step 1: Weigh out 54-60 parts Fe powder, 24-26 parts Cr powder, 12-14 parts Ni powder, 3-4 parts Al powder, 1.2-1.8 parts Ti powder, 0.10-0.13 parts Y powder, 1.0-1.2 parts Si powder, 0.7-1.0 parts Mo powder, and 0.003-0.005 parts B powder by weight, and set aside. Step 2: Dry the Cr powder, Ni powder, Al powder, Ti powder, Y powder, Si powder, Mo powder, Fe powder and B powder separately at a drying temperature of 100-120℃ for 2-3 hours. After drying, put them into a mixer and mix them for 3-5 hours under argon protection at a mixing speed of 200-300 r / min to obtain the core powder. Step 3: Place the H1Cr21Ni10Mn6 stainless steel strip into a forming machine and roll it into a U-shaped groove. Fill the U-shaped groove with the core powder, with a filling density of 1.3-1.5 g / cm³. 3 Then, the U-shaped groove is closed by pressing with rollers to obtain the welding wire blank; Step 4: Perform multiple cold drawing processes on the welding wire blank. During the cold drawing process, control the reduction rate of the surface area of each pass to 8-12%, and the cold drawing speed to 1-3 m / min. Use graphite powder as a lubricant during the cold drawing process until the target diameter of 0.5-2.0 mm is drawn. Place the cold-drawn welding wire in an annealing furnace and heat it to 750-900℃ at a heating rate of 6℃ / min under argon protection. Hold it at this temperature for 1.5-2.5 h, and then cool it to room temperature at a cooling rate of 4℃ / min. Finally, use mechanical polishing to polish the surface of the welding wire to a roughness Ra=0.6μm to obtain the basic welding wire. Step 5: Clean the base welding wire with acetone and anhydrous ethanol in sequence using ultrasonic cleaning for 10-15 minutes, then dry it with hot air at 50-60℃. Pass the welding wire through the coating liquid tank at a uniform speed of 1-3 m / min. The coating liquid tank contains welding wire coating liquid. Control the coating thickness to be 3-20 μm. Pre-dry the coated welding wire at 80-100℃ for 10-20 minutes, and then cure it with hot air at 120-150℃ for 30-60 minutes to obtain high-temperature oxidation-resistant welding wire for laser welding.
[0023] The beneficial effects of this invention are: The present invention relates to a high-temperature oxidation-resistant welding wire for laser welding and its preparation process. The process involves drying Cr powder, Ni powder, Al powder, Ti powder, Y powder, Si powder, Mo powder, Fe powder, and B powder separately, then mixing them in a mixer under argon protection to obtain core flux powder. A stainless steel strip is rolled into a U-shaped groove, filled with the core flux powder, and then the U-shaped groove is squeezed closed to obtain a welding wire blank. The welding wire blank undergoes multiple cold drawing passes, followed by annealing and mechanical polishing to obtain a base welding wire. The base welding wire is then ultrasonically cleaned and dried sequentially with acetone and anhydrous ethanol, uniformly coated using a coating liquid bath, and pre-dried and cured with hot air to obtain a high-temperature oxidation-resistant welding wire for laser welding. The high-temperature oxidation-resistant welding wire for laser welding uses a high-temperature alloy core and stainless steel... The synergistic effect of the steel cladding and the high-temperature resistant aromatic polyamide coating results in excellent high-temperature oxidation resistance, welding stability, and reliability. It effectively inhibits the oxidation of welding wire and weld metal in the high-temperature environment of laser welding, reduces welding defects such as porosity, cracks, and inclusions, and significantly improves the strength, toughness, and high-temperature corrosion resistance of the welded joint. The coating is smooth, dense, and has strong adhesion, which can isolate air and moisture, extend the storage life of the welding wire, and reduce wire feeding resistance, ensuring continuous and stable laser welding process and smooth wire feeding. The welding wire has uniform composition, dense structure, and high diameter accuracy, resulting in beautiful weld formation and stable deposited metal properties. It can meet the high-performance requirements of key components for laser-welded joints under high-temperature conditions, and has strong overall practicality and broad application prospects.
[0024] The roles of each element in the flux-cored powder: Cr is the main antioxidant element, preferentially oxidizing at high temperatures to form a dense Cr2O3 oxide film, blocking oxygen diffusion into the molten pool and effectively inhibiting the oxidation of the welding wire and weld metal; Ni enhances the toughness and corrosion resistance of the welding wire, improves the strength-ductility matching of the weld, and works synergistically with Cr to enhance the stability of the oxide film; Al is an auxiliary antioxidant element, working synergistically with Cr to form a Cr2O3-Al2O3 composite oxide film, further improving the high-temperature oxidation resistance of the welding wire. Al also has a deoxidizing effect, reducing the oxygen content in the weld and lowering the probability of porosity defects; Ti has a strong affinity for oxygen and preferentially combines with oxygen in the weld, playing a deoxidizing role and reducing oxide inclusions. i can refine the weld grains, improve the strength and toughness of the weld, and synergistically regulate the oxidation reaction balance with Al, reducing Ti oxidation loss; Y, a rare earth element, can refine the weld grains, improve the weld microstructure, enhance the weld toughness and high-temperature stability, and improve the interfacial bonding strength between the oxide film and the substrate, preventing the oxide film from peeling off at high temperatures, further improving the high-temperature oxidation resistance of the welding wire; Si, as a deoxidizer, can effectively remove oxygen from the weld, reduce oxide inclusions and porosity defects, and improve the weld fluidity and weld formation; Mo can improve the high-temperature strength and corrosion resistance of the welding wire, and improve the service stability of the weld under high-temperature conditions; trace amounts of B can improve the welding process performance of the welding wire, enhance the weld fluidity, and reduce crack defects.
[0025] In the preparation of high-temperature oxidation-resistant welding wire for laser welding, an aromatic polyamide was first prepared. Starting with o-chlorotrifluorotoluene as the starting material, an electrophilic aromatic substitution reaction was first carried out in a nitration system composed of concentrated sulfuric acid and concentrated nitric acid under ice bath temperature control to introduce a nitro group onto the benzene ring of o-chlorotrifluorotoluene, followed by purification to obtain 2-chloro-5-nitrotrifluorotoluene. Then, through an aromatic nucleophilic substitution reaction, under nitrogen protection, with anhydrous potassium carbonate as an acid-binding agent and high temperature conditions, phenoxazine and 2-chloro-5-nitrotrifluorotoluene under CN coupling were obtained to yield intermediate I. Subsequently, through palladium on carbon catalyst catalysis and hydrazine hydrate reduction, the nitro group in intermediate I was reduced to an amino group to obtain intermediate II. Next, intermediate II is coupled with 2-chloro-5-nitrotrifluorotoluene again via an aromatic nucleophilic substitution reaction to obtain intermediate III, which contains nitro groups at both ends. Intermediate III is then reduced a second time by a palladium-on-carbon catalyst to convert the nitro groups to amino groups, yielding an aromatic diamine monomer containing a phenoxazine structure and a trifluoromethyl group. This diamine monomer undergoes low-temperature solution polycondensation with terephthaloyl chloride under nitrogen protection, ice bath temperature control, and pyridine as an acid-binding agent. After precipitation, Soxhlet extraction, and drying, a high-temperature resistant aromatic polyamide with excellent film-forming properties is finally obtained. The aromatic polyamide molecule contains a rigid aromatic ring, a phenoxazine heterocycle, and a trifluoromethyl group in its main chain, exhibiting a highly stable structure. The rigid aromatic ring and the phenoxazine heterocycle... The structure endows the polymer with excellent heat resistance and mechanical strength, making it more thermally stable, with lower smoke emission and less carbonization at high temperatures during laser welding. It can quickly form a continuous and stable high-temperature barrier layer during welding. Trifluoromethyl groups significantly reduce the polymer surface energy, improve hydrophobicity, oxidation resistance and corrosion resistance, and reduce high-temperature oxidation erosion. Amide bonds ensure good adhesion between the coating and the welding wire surface, making it less prone to peeling and detachment. Amide bonds provide good film-forming properties and flexibility, making the coating dense and uniform, with both rigidity and toughness. The molecular structure is symmetrical and regular, with extremely strong chemical stability. It does not react with the flux core or metal matrix, does not introduce impurities, and does not contaminate the weld. This aromatic polymer As a coating for high-temperature oxidation-resistant welding wires used in laser welding, amide has several significant advantages. It can form a uniform, dense, and strongly adherent protective film on the surface of the welding wire, effectively isolating it from air and moisture during long-term storage, preventing corrosion and extending its shelf life. Furthermore, its excellent insulation properties prevent arc shunting during welding, ensuring concentrated welding energy, reducing defects such as porosity and cracks, and significantly improving the quality of welded joints. In addition, the polymer has good compatibility with the welding wire substrate and flux-cored components, does not cause adverse reactions, and does not affect the overall performance of the welding wire. Moreover, its preparation process is simple and cost-controllable, fundamentally improving the high-temperature oxidation resistance, welding stability, and reliability of the welding wire. Detailed Implementation
[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0027] Example 1: This embodiment describes the preparation process of high-temperature oxidation-resistant welding wire for laser welding, including the following steps: Step s1: 0.25 mol o-chlorotrifluorotoluene and 42 mL concentrated sulfuric acid (98% by mass) were added to a single-necked flask. The mixture was stirred for 30 min at 300 r / min under ice bath conditions. Then, 84 mL of a mixed solution (a 1:1 volume mixture of concentrated sulfuric acid and concentrated nitric acid, with a 68% by mass of concentrated nitric acid) was added dropwise. The mixture was then heated to room temperature and the reaction was continued for 3 h. After the reaction was completed, the mixture was extracted in ice water and washed three times with saturated sodium chloride solution. After separation, the lower oily layer was obtained and purified by column chromatography with petroleum ether eluent to obtain 2-chloro-5-nitrotrifluorotoluene. Step s2: 0.2 mol phenoxazine, 0.2 mol anhydrous potassium carbonate and 240 mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. Under the conditions of 75 °C and stirring rate of 300 r / min, 0.2 mol 2-chloro-5-nitrotrifluorotoluene was added. The mixture was heated to 140 °C and reacted for 24 h. After that, the mixture was poured into ice water and allowed to stand to crystallize. After filtration, the solid was placed in a vacuum drying oven and dried at 80 °C for 2 h. The solid was separated and purified by column chromatography with petroleum ether as eluent, and then recrystallized with ethanol to obtain intermediate I. Step s3: Add 0.01 mol of intermediate I, 0.2 g of palladium catalyst on carbon (palladium catalyst with 5% palladium content) and 40 mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube and constant pressure dropping funnel. Purge with nitrogen for protection. Under the conditions of 55 °C and stirring rate of 300 r / min, add 20 mL of hydrazine hydrate dropwise. React for 24 h at 70 °C. Filter while hot, pour the filtrate into ice water to allow crystallization. After filtration, place the solid in a vacuum drying oven and dry at 80 °C for 2 h to obtain intermediate II. Step s4: Add 0.05 mol of intermediate II, 0.1 mol of anhydrous potassium carbonate and 100 mL of N,N-dimethylformamide to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Under conditions of 75 °C and stirring rate of 300 r / min, add 0.12 mol of 2-chloro-5-nitrotrifluorotoluene. React at 140 °C for 24 h. Pour into ice water and let stand to crystallize. Filter and wash with deionized water until neutral. Recrystallize with dichloromethane. After filtration, place the solid in a vacuum drying oven and dry at 80 °C for 2.5 h to obtain intermediate III. Step s5: 0.01 mol intermediate III, 0.2 g palladium on carbon catalyst (palladium on carbon catalyst with 5% palladium content) and 40 mL anhydrous ethanol were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube and constant pressure dropping funnel. Nitrogen gas was introduced for protection. Under the conditions of 55 °C and stirring rate of 300 r / min, 20 mL hydrazine hydrate was added dropwise. The mixture was heated to 70 °C and reacted for 24 h. The mixture was filtered while hot, and the filtrate was poured into ice water to allow crystallization. The crystals were dried under vacuum at 70 °C for 3 h. The diamine monomer was purified by column chromatography with a mixed eluent (a solution of petroleum ether and dichloromethane mixed in a volume ratio of 3:1) to obtain the diamine monomer. Step s6: Add 1 mol of diamine monomer, 1 mol of terephthaloyl chloride and 3.7 L of N,N-dimethylacetamide to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen and stir for 60 min at a stirring rate of 300 r / min under ice bath. Add 0.1 L of pyridine, remove the ice bath and allow to rise naturally to room temperature. Continue stirring and react for 24 h. After the reaction is complete, pour into methanol and stir to precipitate solid. Filter and collect the solid. Extract the solid with methanol at 110 °C for 24 h. After filtration, place the solid in a vacuum drying oven and dry at 85 °C for 4 h to obtain aromatic polyamide. Step s7: Weigh out 54 parts Fe powder, 24 parts Cr powder, 12 parts Ni powder, 3 parts Al powder, 1.2 parts Ti powder, 0.10 parts Y powder, 1.0 part Si powder, 0.7 parts Mo powder, and 0.003 parts B powder by weight, and set aside. Step s8: Dry Cr powder, Ni powder, Al powder, Ti powder, Y powder, Si powder, Mo powder, Fe powder and B powder separately at a drying temperature of 100℃ for 2 hours. After drying, put them into a mixer and mix them for 3 hours under argon protection at a mixing speed of 200r / min to obtain the core powder. Step s9: Place the H1Cr21Ni10Mn6 stainless steel strip into a forming machine and roll it into a U-shaped groove. Fill the U-shaped groove with the core powder, with a filling density of 1.3 g / cm³. 3Then, the U-shaped groove is closed by pressing with rollers to obtain the welding wire blank; Step s10: The welding wire blank is subjected to multiple cold drawing processes. During the cold drawing process, the reduction rate of each pass is controlled at 8%, the cold drawing speed is 1m / min, and graphite powder is used as a lubricant during the cold drawing process until the target diameter of 0.5mm is drawn. The cold-drawn welding wire is placed in an annealing furnace and heated to 750℃ at a heating rate of 6℃ / min under argon protection. It is held at this temperature for 1.5h and then cooled to room temperature at a cooling rate of 4℃ / min. After that, mechanical polishing is used to polish the surface of the welding wire to a roughness Ra=0.6μm to obtain the basic welding wire. Step s11: The base welding wire is ultrasonically cleaned with acetone and anhydrous ethanol for 10 minutes in sequence, and then dried with hot air at 50°C. The welding wire is passed through the coating liquid tank at a speed of 1 m / min. The coating liquid tank contains 500 mL of welding wire coating liquid (a welding wire coating liquid prepared by aromatic polyamide resin and N,N-dimethylacetamide at a ratio of 1 g: 9 mL). The coating thickness is controlled to be 3 μm. The coated welding wire is pre-dried at 80°C for 10 minutes, and then cured with hot air at 120°C for 30 minutes to obtain high-temperature anti-oxidation welding wire for laser welding.
[0028] Example 2: This embodiment describes the preparation process of high-temperature oxidation-resistant welding wire for laser welding, including the following steps: Step s1: 0.374 mol o-chlorotrifluorotoluene and 63 mL concentrated sulfuric acid (98% by mass) were added to a single-necked flask. The mixture was stirred for 33 min at 350 r / min under ice bath conditions. Then, 126 mL of a mixed solution (a 1:1 volume mixture of concentrated sulfuric acid and concentrated nitric acid, with a 68% by mass of concentrated nitric acid) was added dropwise. The mixture was then heated to room temperature and the reaction was continued for 4 h. After the reaction was completed, the mixture was extracted in ice water and washed three times with saturated sodium chloride solution. After separation, the lower oily layer was obtained and purified by column chromatography with petroleum ether eluent to obtain 2-chloro-5-nitrotrifluorotoluene. Step s2: 0.3 mol phenoxazine, 0.3 mol anhydrous potassium carbonate, and 360 mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Nitrogen gas was introduced for protection. Under the conditions of 77 °C and stirring rate of 350 r / min, 0.3 mol 2-chloro-5-nitrotrifluorotoluene was added. The mixture was heated to 145 °C and reacted for 24.5 h. After that, the mixture was poured into ice water and allowed to stand to crystallize. After filtration, the solid was placed in a vacuum drying oven and dried at 83 °C for 2.5 h. The solid was purified by column chromatography with petroleum ether as eluent and then recrystallized with ethanol to obtain intermediate I. Step s3: Add 0.015 mol of intermediate I, 0.3 g of palladium catalyst on carbon (palladium catalyst with 5% palladium content) and 60 mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube and constant pressure dropping funnel. Purge with nitrogen for protection. Under the conditions of 57 °C and stirring rate of 350 r / min, add 30 mL of hydrazine hydrate dropwise. React for 24.5 h at 75 °C. Filter while hot, pour the filtrate into ice water and let it stand to crystallize. After filtration, place the solid in a vacuum drying oven and dry at 83 °C for 2.5 h to obtain intermediate II. Step s4: Add 0.075 mol of intermediate II, 0.15 mol of anhydrous potassium carbonate and 150 mL of N,N-dimethylformamide to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Under conditions of 77 °C and stirring rate of 350 r / min, add 0.18 mol of 2-chloro-5-nitrotrifluorotoluene. React at 145 °C for 24.5 h. Pour into ice water and let stand to crystallize. Filter and wash with deionized water until neutral. Recrystallize with dichloromethane. After filtration, place the solid in a vacuum drying oven and dry at 83 °C for 3 h to obtain intermediate III. Step s5: 0.015 mol intermediate III, 0.3 g palladium on carbon catalyst (5% palladium content) and 60 mL anhydrous ethanol were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube and constant pressure dropping funnel. Nitrogen gas was introduced for protection. Under the conditions of 57 °C and stirring rate of 350 r / min, 30 mL hydrazine hydrate was added dropwise. The mixture was heated to 75 °C and reacted for 24.5 h. The mixture was filtered while hot, and the filtrate was poured into ice water to allow crystallization. The crystals were dried under vacuum at 75 °C for 3.5 h. The diamine monomer was purified by column chromatography with a mixed eluent (a solution of petroleum ether and dichloromethane in a volume ratio of 3:1) to obtain the diamine monomer. Step s6: 1.5 mol of diamine monomer, 1.5 mol of terephthaloyl chloride and 5.55 L of N,N-dimethylacetamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred for 65 min at a stirring rate of 350 r / min under ice bath conditions. 0.15 L of pyridine was added. The ice bath was removed and the mixture was allowed to rise naturally to room temperature. The reaction was continued for 24.5 h. After the reaction was completed, the mixture was poured into methanol and stirred to precipitate a solid. The solid was collected by filtration and extracted with methanol at 110 °C for 24 h. After filtration, the solid was placed in a vacuum drying oven and dried at 87 °C for 4.5 h to obtain aromatic polyamide. Step s7: Weigh out 57 parts Fe powder, 25 parts Cr powder, 13 parts Ni powder, 3.5 parts Al powder, 1.5 parts Ti powder, 0.115 parts Y powder, 1.1 parts Si powder, 0.85 parts Mo powder, and 0.004 parts B powder by weight, and set aside. Step s8: Dry Cr powder, Ni powder, Al powder, Ti powder, Y powder, Si powder, Mo powder, Fe powder and B powder separately at a drying temperature of 110℃ for 2.5h. After drying, put them into a mixer and mix them for 4h under argon protection at a mixing speed of 250r / min to obtain the core powder. Step s9: Place the H1Cr21Ni10Mn6 stainless steel strip into a forming machine and roll it into a U-shaped groove. Fill the U-shaped groove with the core powder, with a filling density of 1.4 g / cm³. 3 Then, the U-shaped groove is closed by pressing with rollers to obtain the welding wire blank; Step s10: The welding wire blank is subjected to multiple cold drawing processes. During the cold drawing process, the surface reduction rate of each pass is controlled at 10%, the cold drawing speed is 2m / min, and graphite powder is used as a lubricant during the cold drawing process until the target diameter of 1mm is drawn. The cold-drawn welding wire is placed in an annealing furnace and heated to 820℃ at a heating rate of 6℃ / min under argon protection. It is held at this temperature for 2 hours and then cooled to room temperature at a cooling rate of 4℃ / min. After that, mechanical polishing is used to polish the surface of the welding wire to a roughness Ra=0.6μm to obtain the basic welding wire. Step s11: The base welding wire is ultrasonically cleaned with acetone and anhydrous ethanol for 13 minutes in sequence, and then dried with hot air at 55℃. The welding wire is passed through the coating liquid tank at a speed of 2m / min. The coating liquid tank contains 520mL of welding wire coating liquid (a welding wire coating liquid prepared by aromatic polyamide resin and N,N-dimethylacetamide at a ratio of 1g:9mL). The coating thickness is controlled to be 10μm. The coated welding wire is pre-dried at 90℃ for 15 minutes, and then cured with hot air at 130℃ for 45 minutes to obtain high-temperature anti-oxidation welding wire for laser welding.
[0029] Example 3: This embodiment describes the preparation process of high-temperature oxidation-resistant welding wire for laser welding, including the following steps: Step s1: 0.50 mol o-chlorotrifluorotoluene and 84 mL concentrated sulfuric acid (98% by mass) were added to a single-necked flask. The mixture was stirred for 35 min at a stirring rate of 400 r / min under ice bath conditions. Then, 168 mL of a mixed solution (a solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1, with a 68% by mass of concentrated nitric acid) was added dropwise. The mixture was then heated to room temperature and the reaction was continued for 5 h. After the reaction was completed, the mixture was extracted in ice water and washed three times with saturated sodium chloride solution. After separation, the lower oily layer was obtained and purified by column chromatography with petroleum ether eluent to obtain 2-chloro-5-nitrotrifluorotoluene. Step s2: 0.4 mol phenoxazine, 0.4 mol anhydrous potassium carbonate and 480 mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. Under the conditions of 80 °C and stirring rate of 400 r / min, 0.4 mol 2-chloro-5-nitrotrifluorotoluene was added. The mixture was heated to 150 °C and reacted for 25 h. After that, the mixture was poured into ice water and allowed to stand to crystallize. After filtration, the solid was placed in a vacuum drying oven and dried at 85 °C for 3 h. The solid was purified by column chromatography with petroleum ether as eluent and then recrystallized with ethanol to obtain intermediate I. Step s3: Add 0.02 mol of intermediate I, 0.4 g of palladium catalyst on carbon (palladium catalyst with 5% palladium content) and 80 mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube and constant pressure dropping funnel. Purge with nitrogen for protection. Under the conditions of 60 °C and stirring rate of 400 r / min, add 40 mL of hydrazine hydrate dropwise. React for 25 h at 80 °C. Filter while hot, pour the filtrate into ice water to allow crystallization. After filtration, place the solid in a vacuum drying oven and dry at 85 °C for 3 h to obtain intermediate II. Step s4: Add 0.10 mol of intermediate II, 0.2 mol of anhydrous potassium carbonate, and 200 mL of N,N-dimethylformamide to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection. Under conditions of 80 °C and a stirring rate of 400 r / min, add 0.24 mol of 2-chloro-5-nitrotrifluorotoluene. React at 150 °C for 25 h. Pour the mixture into ice water and allow it to stand to crystallize. Filter and wash with deionized water until neutral. Recrystallize with dichloromethane. After filtration, place the solid in a vacuum drying oven and dry at 85 °C for 3.5 h to obtain intermediate III. Step s5: 0.02 mol intermediate III, 0.4 g palladium on carbon catalyst (palladium on carbon catalyst with 5% palladium content) and 80 mL anhydrous ethanol were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube and constant pressure dropping funnel. Nitrogen gas was introduced for protection. Under the conditions of 60 °C and stirring rate of 400 r / min, 40 mL hydrazine hydrate was added dropwise. The mixture was heated to 80 °C and reacted for 25 h. The mixture was filtered while hot, and the filtrate was poured into ice water to allow crystallization. The crystals were dried under vacuum at 80 °C for 4 h. The diamine monomer was purified by column chromatography with a mixed eluent (a solution of petroleum ether and dichloromethane mixed in a volume ratio of 3:1) to obtain the diamine monomer. Step s6: Add 2 mol of diamine monomer, 2 mol of terephthaloyl chloride and 7.4 L of N,N-dimethylacetamide to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen and stir for 70 min at a stirring rate of 400 r / min under ice bath conditions. Add 0.2 L of pyridine, remove the ice bath and allow to rise naturally to room temperature. Continue stirring and react for 25 h. After the reaction is complete, pour into methanol and stir to precipitate solid. Filter and collect the solid. Extract the solid with methanol at 110 °C for 24 h. After filtration, place the solid in a vacuum drying oven and dry at 90 °C for 5 h to obtain aromatic polyamide. Step s7: Weigh out 60 parts Fe powder, 26 parts Cr powder, 14 parts Ni powder, 4 parts Al powder, 1.8 parts Ti powder, 0.13 parts Y powder, 1.2 parts Si powder, 1.0 part Mo powder, and 0.005 parts B powder by weight, and set aside. Step s8: Dry Cr powder, Ni powder, Al powder, Ti powder, Y powder, Si powder, Mo powder, Fe powder and B powder separately at a drying temperature of 120℃ for 3 hours. After drying, put them into a mixer and mix them for 5 hours under argon protection at a mixing speed of 300 r / min to obtain the core powder. Step s9: Place the H1Cr21Ni10Mn6 stainless steel strip into a forming machine and roll it into a U-shaped groove. Fill the U-shaped groove with the core powder, with a filling density of 1.5 g / cm³. 3 Then, the U-shaped groove is closed by pressing with rollers to obtain the welding wire blank; Step s10: The welding wire blank is subjected to multiple cold drawing processes. During the cold drawing process, the surface reduction rate of each pass is controlled at 12%, the cold drawing speed is 3m / min, and graphite powder is used as a lubricant during the cold drawing process until the target diameter of 2.0mm is drawn. The cold-drawn welding wire is placed in an annealing furnace and heated to 900℃ at a heating rate of 6℃ / min under argon protection. It is held at this temperature for 2.5h, and then cooled to room temperature at a cooling rate of 4℃ / min. After that, mechanical polishing is used to polish the surface of the welding wire to a roughness Ra=0.6μm to obtain the basic welding wire. Step s11: The base welding wire is ultrasonically cleaned with acetone and anhydrous ethanol for 15 minutes in sequence, and then dried with hot air at 60°C. The welding wire is passed through the coating liquid tank at a speed of 3 m / min. The coating liquid tank contains 550 mL of welding wire coating liquid (a welding wire coating liquid prepared by aromatic polyamide resin and N,N-dimethylacetamide at a ratio of 1 g: 9 mL). The coating thickness is controlled to be 20 μm. The coated welding wire is pre-dried at 100°C for 20 minutes, and then cured with hot air at 150°C for 60 minutes to obtain high-temperature anti-oxidation welding wire for laser welding.
[0030] Comparative Example 1: This comparative example illustrates the preparation process of high-temperature oxidation-resistant welding wire for laser welding, including the following steps: Step s1: Weigh out 54 parts Fe powder, 24 parts Cr powder, 12 parts Ni powder, 3 parts Al powder, 1.2 parts Ti powder, 0.10 parts Y powder, 1.0 part Si powder, 0.7 parts Mo powder, and 0.003 parts B powder by weight, and set aside. Step s2: Dry Cr powder, Ni powder, Al powder, Ti powder, Y powder, Si powder, Mo powder, Fe powder and B powder separately at a drying temperature of 100℃ for 2 hours. After drying, put them into a mixer and mix them for 3 hours under argon protection at a mixing speed of 200r / min to obtain the core powder. Step s3: Place the H1Cr21Ni10Mn6 stainless steel strip into a forming machine and roll it into a U-shaped groove. Fill the U-shaped groove with the core powder, with a filling density of 1.3 g / cm³. 3 Then, the U-shaped groove is closed by pressing with rollers to obtain the welding wire blank; Step s4: The welding wire blank is subjected to multiple cold drawing processes. During the cold drawing process, the reduction rate of each pass is controlled at 8%, the cold drawing speed is 1m / min, and graphite powder is used as a lubricant. The drawing continues until the target diameter of 0.5mm is reached. The cold-drawn welding wire is then placed in an annealing furnace and heated to 750℃ at a heating rate of 6℃ / min under argon protection. The temperature is held for 1.5h, and then cooled to room temperature at a cooling rate of 4℃ / min. Finally, the surface of the welding wire is polished to a roughness of Ra=0.6μm by mechanical polishing to obtain a high-temperature oxidation-resistant welding wire for laser welding.
[0031] Comparative Example 2: This comparative example illustrates the preparation process of high-temperature oxidation-resistant welding wire for laser welding, including the following steps: Step s1: 0.25 mol o-chlorotrifluorotoluene and 42 mL concentrated sulfuric acid (98% by mass) were added to a single-necked flask. The mixture was stirred for 30 min at 300 r / min under ice bath conditions. Then, 84 mL of a mixed solution (a 1:1 volume mixture of concentrated sulfuric acid and concentrated nitric acid, with a 68% by mass of concentrated nitric acid) was added dropwise. The mixture was then heated to room temperature and the reaction was continued for 3 h. After the reaction was completed, the mixture was extracted in ice water and washed three times with saturated sodium chloride solution. After separation, the lower oily layer was obtained and purified by column chromatography with petroleum ether eluent to obtain 2-chloro-5-nitrotrifluorotoluene. Step s2: 0.2 mol phenoxazine, 0.2 mol anhydrous potassium carbonate and 240 mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. Under the conditions of 75 °C and stirring rate of 300 r / min, 0.2 mol 2-chloro-5-nitrotrifluorotoluene was added. The mixture was heated to 140 °C and reacted for 24 h. After that, the mixture was poured into ice water and allowed to stand to crystallize. After filtration, the solid was placed in a vacuum drying oven and dried at 80 °C for 2 h. The solid was separated and purified by column chromatography with petroleum ether as eluent, and then recrystallized with ethanol to obtain intermediate I. Step s3: Add 0.01 mol of intermediate I, 0.2 g of palladium catalyst on carbon (palladium catalyst with 5% palladium content) and 40 mL of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube and constant pressure dropping funnel. Purge with nitrogen for protection. Under the conditions of 55 °C and stirring rate of 300 r / min, add 20 mL of hydrazine hydrate dropwise. React for 24 h at 70 °C. Filter while hot, pour the filtrate into ice water to allow crystallization. After filtration, place the solid in a vacuum drying oven and dry at 80 °C for 2 h to obtain intermediate II. Step s4: Add 0.05 mol of intermediate II, 0.1 mol of anhydrous potassium carbonate and 100 mL of N,N-dimethylformamide to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Under conditions of 75 °C and stirring rate of 300 r / min, add 0.12 mol of 2-chloro-5-nitrotrifluorotoluene. React at 140 °C for 24 h. Pour into ice water and let stand to crystallize. Filter and wash with deionized water until neutral. Recrystallize with dichloromethane. After filtration, place the solid in a vacuum drying oven and dry at 80 °C for 2.5 h to obtain intermediate III. Step s5: 0.01 mol intermediate III, 0.2 g palladium on carbon catalyst (palladium on carbon catalyst with 5% palladium content) and 40 mL anhydrous ethanol were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube and constant pressure dropping funnel. Nitrogen gas was introduced for protection. Under the conditions of 55 °C and stirring rate of 300 r / min, 20 mL hydrazine hydrate was added dropwise. The mixture was heated to 70 °C and reacted for 24 h. The mixture was filtered while hot, and the filtrate was poured into ice water to allow crystallization. The crystals were dried under vacuum at 70 °C for 3 h. The diamine monomer was purified by column chromatography with a mixed eluent (a solution of petroleum ether and dichloromethane mixed in a volume ratio of 3:1) to obtain the diamine monomer. Step s6: Add 1 mol of diamine monomer, 1 mol of terephthaloyl chloride and 3.7 L of N,N-dimethylacetamide to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen and stir for 60 min at a stirring rate of 300 r / min under ice bath. Add 0.1 L of pyridine, remove the ice bath and allow to rise naturally to room temperature. Continue stirring and react for 24 h. After the reaction is complete, pour into methanol and stir to precipitate solid. Filter and collect the solid. Extract the solid with methanol at 110 °C for 24 h. After filtration, place the solid in a vacuum drying oven and dry at 85 °C for 4 h to obtain aromatic polyamide. Step s7: Weigh out 54 parts Fe powder, 20 parts Cr powder, 12 parts Ni powder, 3 parts Al powder, 1.2 parts Ti powder, 1.0 part Si powder, 0.7 parts Mo powder, and 0.003 parts B powder by weight, and set aside. Step s8: Dry Cr powder, Ni powder, Al powder, Ti powder, Si powder, Mo powder, Fe powder and B powder separately at a drying temperature of 100℃ for 2 hours. After drying, put them into a mixer and mix them for 3 hours under argon protection at a mixing speed of 200r / min to obtain the core powder. Step s9: Place the H1Cr21Ni10Mn6 stainless steel strip into a forming machine and roll it into a U-shaped groove. Fill the U-shaped groove with the core powder, with a filling density of 1.3 g / cm³. 3 Then, the U-shaped groove is closed by pressing with rollers to obtain the welding wire blank; Step s10: The welding wire blank is subjected to multiple cold drawing processes. During the cold drawing process, the reduction rate of each pass is controlled at 8%, the cold drawing speed is 1m / min, and graphite powder is used as a lubricant during the cold drawing process until the target diameter of 0.5mm is drawn. The cold-drawn welding wire is placed in an annealing furnace and heated to 750℃ at a heating rate of 6℃ / min under argon protection. It is held at this temperature for 1.5h and then cooled to room temperature at a cooling rate of 4℃ / min. After that, mechanical polishing is used to polish the surface of the welding wire to a roughness Ra=0.6μm to obtain the basic welding wire. Step s11: The base welding wire is ultrasonically cleaned with acetone and anhydrous ethanol for 10 minutes in sequence, and then dried with hot air at 50°C. The welding wire is passed through the coating liquid tank at a speed of 1 m / min. The coating liquid tank contains 500 mL of welding wire coating liquid (a welding wire coating liquid prepared by aromatic polyamide resin and N,N-dimethylacetamide at a ratio of 1 g: 9 mL). The coating thickness is controlled to be 3 μm. The coated welding wire is pre-dried at 80°C for 10 minutes, and then cured with hot air at 120°C for 30 minutes to obtain high-temperature anti-oxidation welding wire for laser welding.
[0032] Comparative Example 3: This comparative example illustrates the preparation process of high-temperature oxidation-resistant welding wire for laser welding, including the following steps: Step s1: Weigh out 54 parts Fe powder, 20 parts Cr powder, 12 parts Ni powder, 3 parts Al powder, 1.2 parts Ti powder, 1.0 part Si powder, 0.7 parts Mo powder, and 0.003 parts B powder by weight, and set aside. Step s2: Dry Cr powder, Ni powder, Al powder, Ti powder, Si powder, Mo powder, Fe powder and B powder separately at a drying temperature of 100℃ for 2 hours. After drying, put them into a mixer and mix them for 3 hours under argon protection at a mixing speed of 200r / min to obtain the core powder. Step s3: Place the H1Cr21Ni10Mn6 stainless steel strip into a forming machine and roll it into a U-shaped groove. Fill the U-shaped groove with the core powder, with a filling density of 1.3 g / cm³. 3 Then, the U-shaped groove is closed by pressing with rollers to obtain the welding wire blank; Step s4: The welding wire blank is subjected to multiple cold drawing processes. During the cold drawing process, the reduction rate of each pass is controlled at 8%, the cold drawing speed is 1m / min, and graphite powder is used as a lubricant. The drawing continues until the target diameter of 0.5mm is reached. The cold-drawn welding wire is then placed in an annealing furnace and heated to 750℃ at a heating rate of 6℃ / min under argon protection. The temperature is held for 1.5h, and then cooled to room temperature at a cooling rate of 4℃ / min. Finally, the surface of the welding wire is polished to a roughness of Ra=0.6μm by mechanical polishing to obtain a high-temperature oxidation-resistant welding wire for laser welding.
[0033] Performance testing: The high-temperature oxidation-resistant welding wires for laser welding in Examples 1-3 and Comparative Examples 1-3 were tested according to the following methods; High-temperature antioxidant performance test: The weight gain method was used. Each sample was cut into 10mm×5mm×0.5mm sizes, washed with acetone, dried and weighed (recorded as m0). The samples were placed in a high-temperature chamber and kept at 850℃ for 100h. After being taken out and cooled to room temperature, they were weighed again (recorded as m1). The oxidation weight gain rate was calculated as (m1-m0) / m0×100%. The lower the weight gain rate, the better the high-temperature antioxidant performance.
[0034] Mechanical property testing of welded joints: Each sample was welded to a Q235 steel plate (5mm thick) using a laser welding machine with a laser power of 3000W and a welding speed of 2m / min. The shielding gas was argon gas with a flow rate of 15L / min. After welding, tensile test specimens and V-notch impact test specimens were prepared according to standards. The tensile strength of the welded joint was tested using a universal testing machine, and the room temperature impact toughness was tested using an impact testing machine.
[0035] Welding defect rate test: The welded joints of each sample were observed under a metallographic microscope at 100x magnification. The number of pores, cracks and inclusions within each 100mm weld length was counted, and the defect rate was calculated. Defect rate = (total number of defects / total weld length) × 100%. The lower the defect rate, the better the welding stability.
[0036] The test results are shown in Table 1: Table 1: Test Results Summary Table
[0037] Referring to Table 1, a comparison between Examples 1-3 and Comparative Examples 1-3 shows that Example 1 exhibits the lowest high-temperature oxidation weight gain, indicating that the aromatic polyamide coating and the core elements (Cr, Y, etc.) work synergistically to effectively block high-temperature oxidation. The welded joint exhibits the highest tensile strength, impact toughness, and lowest defect rate, demonstrating that the welding wire structure, component ratio, and preparation process of this invention are reasonable and can significantly improve welding performance. The high-temperature anti-oxidation welding wire for laser welding possesses excellent high-temperature anti-oxidation properties, stable welding process performance, and good mechanical properties.
[0038] Based on the comparison between Example 1 and Comparative Example 1, it can be seen that Comparative Example 1 has no coating, and all its performance is very poor, with a significantly increased welding defect rate. This indicates that the aromatic polyamide coating can effectively isolate oxygen, reduce welding defects, and improve the high-temperature resistance and welding stability of the welding wire.
[0039] Based on the comparison between Example 1 and Comparative Example 2, it can be seen that Comparative Example 2, which does not add Y powder and reduces the Cr content, has a higher oxidation weight gain rate and defect rate than Example 1, and its mechanical properties are reduced. This indicates that Y powder can improve the adhesion of the oxide film and refine the grains. As the main antioxidant element, insufficient Cr powder content will lead to the deterioration of antioxidant performance and mechanical properties.
[0040] Based on the comparison between Example 1 and Comparative Example 3, it can be seen that Comparative Example 3, which has no coating, no added Y powder, and reduced Cr content, has the worst performance in all aspects. The mechanical properties and defect rate of the welded joint are worse than those of Comparative Example 1 and Comparative Example 2. This shows that the coating works synergistically with Cr and Y elements, and none of them can be missing. Without the coating, oxygen cannot be isolated. Without Y powder and with insufficient Cr content, a stable anti-oxidation film cannot be formed. The combination of the two will lead to a significant deterioration in the high-temperature oxidation resistance and welding performance of the welding wire.
[0041] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0042] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.
Claims
1. A high-temperature oxidation-resistant welding wire for laser welding, characterized in that, It consists of a core powder, an outer coating, and a coating layer; The core powder comprises the following components in parts by weight: Fe powder 54-60 parts, Cr powder 24-26 parts, Ni powder 12-14 parts, Al powder 3-4 parts, Ti powder 1.2-1.8 parts, Y powder 0.10-0.13 parts, Si powder 1.0-1.2 parts, Mo powder 0.7-1.0 parts, B powder 0.003-0.005 parts; The outer cladding is made of H1Cr21Ni10Mn6 stainless steel strip; The coating is applied to the outer surface of the outer skin and is an aromatic polyamide resin. The coating is prepared by coating a welding wire coating solution made of aromatic polyamide resin and N,N-dimethylacetamide at a ratio of 1g:9mL. The aromatic polyamide is prepared by the following steps: Step a1: Mix o-chlorotrifluorotoluene and concentrated sulfuric acid, stir, and then add the mixture dropwise. After raising the temperature to room temperature, continue the reaction, extract, wash, separate and purify to obtain 2-chloro-5-nitrotrifluorotoluene; Step a2: Mix phenoxazine, anhydrous potassium carbonate and N,N-dimethylformamide, add 2-chloro-5-nitrotrifluorotoluene, heat to react, allow to stand to crystallize, filter, dry, separate and purify, recrystallize to obtain intermediate I; Step a3: Mix intermediate I, palladium on carbon catalyst and anhydrous ethanol, add hydrazine hydrate dropwise, heat to react, filter while hot, let stand to crystallize, filter and dry to obtain intermediate II; Step a4: Mix intermediate II, anhydrous potassium carbonate and N,N-dimethylformamide, add 2-chloro-5-nitrotrifluorotoluene and heat to react, let stand to crystallize, filter and wash, recrystallize, filter and dry to obtain intermediate III; Step a5: Mix intermediate III, palladium on carbon catalyst and anhydrous ethanol, add hydrazine hydrate dropwise, heat to react, filter while hot, allow to stand to crystallize, dry under vacuum, and purify by column chromatography to obtain diamine monomer; Step a6: Mix the diamine monomer, terephthaloyl chloride and N,N-dimethylacetamide, stir, add pyridine, continue stirring to react, pour into methanol and stir to precipitate solid, filter, Soxhlet extract, filter and dry to obtain aromatic polyamide.
2. The high-temperature oxidation-resistant welding wire for laser welding according to claim 1, characterized in that, In step a1, the ratio of o-chlorotrifluorotoluene, concentrated sulfuric acid, and the mixed solution is 0.25-0.50 mol: 42-84 mL: 84-168 mL; the mixed solution is a solution of concentrated sulfuric acid and concentrated nitric acid mixed in a volume ratio of 1:1; the mass fraction of the concentrated sulfuric acid is 98%; and the mass fraction of the concentrated nitric acid is 68%.
3. The high-temperature oxidation-resistant welding wire for laser welding according to claim 1, characterized in that, The ratio of phenoxazine, anhydrous potassium carbonate, N,N-dimethylformamide and 2-chloro-5-nitrotrifluorotoluene used in step a2 is 0.2-0.4 mol: 0.2-0.4 mol: 240-480 mL: 0.2-0.4 mol.
4. The high-temperature oxidation-resistant welding wire for laser welding according to claim 1, characterized in that, In step a3, the ratio of intermediate I, palladium catalyst on carbon, anhydrous ethanol, and hydrazine hydrate is 0.01-0.02 mol: 0.2-0.4 g: 40-80 mL: 20-40 mL; the palladium catalyst on carbon has a palladium content of 5%.
5. The high-temperature oxidation-resistant welding wire for laser welding according to claim 1, characterized in that, The ratio of intermediate II, anhydrous potassium carbonate, N,N-dimethylformamide and 2-chloro-5-nitrotrifluorotoluene in step a4 is 0.05-0.10 mol: 0.1-0.2 mol: 100-200 mL: 0.12-0.24 mol.
6. The high-temperature oxidation-resistant welding wire for laser welding according to claim 1, characterized in that, In step a5, the ratio of intermediate III, palladium on carbon catalyst, anhydrous ethanol, and hydrazine hydrate is 0.01-0.02 mol: 0.2-0.4 g: 40-80 mL: 20-40 mL; the palladium on carbon catalyst has a palladium content of 5%.
7. The high-temperature oxidation-resistant welding wire for laser welding according to claim 1, characterized in that, The ratio of the diamine monomer, terephthaloyl chloride, N,N-dimethylacetamide and pyridine used in step a6 is 1-2 mol: 1-2 mol: 3.7-7.4 L: 0.1-0.2 L.
8. A process for preparing high-temperature oxidation-resistant welding wire for laser welding, characterized in that, The method for preparing the high-temperature oxidation-resistant welding wire for laser welding as described in any one of claims 1-7 comprises the following steps: Step 1: Weigh out 54-60 parts Fe powder, 24-26 parts Cr powder, 12-14 parts Ni powder, 3-4 parts Al powder, 1.2-1.8 parts Ti powder, 0.10-0.13 parts Y powder, 1.0-1.2 parts Si powder, 0.7-1.0 parts Mo powder, and 0.003-0.005 parts B powder by weight, and set aside. Step 2: Dry the Cr powder, Ni powder, Al powder, Ti powder, Y powder, Si powder, Mo powder, Fe powder and B powder separately, and then mix them in a mixer to obtain the core powder. Step 3: Roll the H1Cr21Ni10Mn6 stainless steel strip into a U-shaped groove, fill the core powder into the U-shaped groove, and then close the U-shaped groove by pressing with rollers to obtain the welding wire blank; Step 4: The welding wire blank is cold-drawn in multiple passes. Graphite powder is used as a lubricant during the cold drawing process until it is drawn to the target diameter. The cold-drawn welding wire is then placed in an annealing furnace, cooled, and then mechanically polished to obtain the basic welding wire. Step 5: Clean the base welding wire with acetone and anhydrous ethanol in sequence using ultrasonic cleaning, then dry it with hot air. Pass the welding wire through a coating liquid tank containing welding wire coating liquid. Pre-dry the coated welding wire and then cure it with hot air to obtain high-temperature oxidation-resistant welding wire for laser welding.